GLYPTAL SYNTHESIS FROM GLYCEROL AND PHTHALIC ANHYDRIDE USING ACTIVATED ZEOLITE AS HETEROGENEOUS CATALYST AND ITS COMPARISON TO HOMOGENEOUS p-TOLUENESULFONIC ACID CATALYST (Jurnal Bahan Alam Terbarukan, 2017)
The abundance of glycerol as the side product of biodiesel has motivated researches on glycerol utilization as a feedstock for more valuable products. This research presents the possibility of producing polyester (glyptal), which is a widely used coating material, from glycerol by esterification using phthalic anhydride. Esterification reaction of phthalic anhydride and glycerol to produce glyptal can be catalyzed by Lewis acid provided by either homogeneous or heterogeneous catalyst. This study compared the performance of activated zeolite as heterogeneous catalyst in the esterification of glycerol and phthalic anhydride with the performance of p-toluenesulfonic acid (PTSA) as homogeneous catalyst. The reactions were carried out in laboratory scale batch reactor. The kinetics was modeled using Step Growth Polymerization Model. The rate constant obtained from experimental data fitting on the model was correlated with temperature by Arrhenius equation. Both activated zeolite and PTSA exhibited Arrhenius behavior. Based on the comparison of the Arrhenius constants of the reaction catalyzed by each of the two different catalysts, PTSA performed better in term of lower activation energy. Nevertheless, this result did not suggest that activated zeolite was failed. The activated zeolite was successful to make the reaction happen. To reach the same performance as the homogeneous PTSA, the activated zeolite needs to be improved with respect to its cation exchange capacity and also the operational consideration such as the amount of zeolite added per volume of reaction and the intensity of mixing to minimize the diffusion resistance surrounding the zeolite particles.